Inter‐domain electron transfer in cellobiose dehydrogenase: modulation by pH and divalent cations. (16th May 2015) - Kracher, Daniel; Zahma, Kawah; Schulz, Christopher; Sygmund, Christoph; Gorton, Lo; Ludwig, Roland
<x xml:space="preserve">Abstract</x> The flavocytochrome cellobiose dehydrogenase (CDH) is secreted by wood‐decomposing fungi, and is the only known extracellular enzyme with the characteristics of an electron transfer protein. Its proposed function is reduction of lytic polysaccharide mono‐oxygenase for subsequent cellulose depolymerization. Electrons are transferred from FADH2 in the catalytic flavodehydrogenase domain of CDH to haem b in a mobile cytochrome domain, which acts as a mediator and transfers electrons towards the active site of lytic polysaccharide mono‐oxygenase to activate oxygen. This vital role of the cytochrome domain is little understood, e.g. why do CDHs exhibit different pH optima and rates for inter‐domain electron transfer (IET)? This study uses kinetic techniques and docking to assess the interaction of both domains and the resulting IET with regard to pH and ions. The results show that the reported elimination of IET at neutral or alkaline pH is caused by electrostatic repulsion, which prevents adoption of the closed conformation of CDH. Divalent alkali earth metal cations are shown to exert a bridging effect between the domains at concentrations of > 3 mm, thereby neutralizing electrostatic repulsion and increasing IET rates. The necessary high ion concentration, together with the docking results, show that this effect is not caused by specific cation binding sites, but by various clusters of Asp, Glu, Asn, Gln and the haem b propionate group at the domain interface. The results show that a closed conformation of both CDH domains is necessary for IET, but the closed conformation also increases the FAD reduction rate by an electron pulling effect.